School Gardens in Poland – Rediscovered Places - Ziemkowska , Joanna (Studia Ecologiae et Bioethicae, 2023)
School gardens have been present in the educational space of the Polish school for many years. In recent decades, however, they have ceased to be appreciated. Efforts have been made to modernize laboratories, they have been equipped with measuring instruments, digital devices and multimedia equipment. A natural laboratory, which a garden in fact is, has become a symbol of the past. It remained only in few schools, performing rather an aesthetic function, less often didactic or educational one. The present article depicts a historical outline, shows earlier and currently noticed possibilities of using school gardens in Poland. An analysis of previous studies on gardens is presented as well. A contemporary design of a school garden was proposed to prepare students of pedagogical faculties for activities in the garden with children. School gardens may contribute to the prevention of “nature deficit” (Louv 2014, 54), they may give a sense of closeness to nature also in urban realities[1]. M. Vogt-Kostecka notes that the fear of dirt, wind and ticks limits children's free play in a meadow and in a forest. Limited access to nature is particularly visible among urban children (Vogt-Kostecka 2017, 11). Gradually, the view of school gardens has been changing and their therapeutic potential (hortitherapy) is noticed. [1] According to R. Louv, the nature deficit is manifested in problems with concentration of attention, hyperactivity, and reduced psychophysical fitness.